Confined phosphorus in carbon nanotube-backboned mesoporous carbon as superior anode material for sodium/potassium-ion batteries. (October 2018) - Liu, Dan; Huang, Xingkang; Qu, Deyu; Zheng, Dong; Wang, Gongwei; Harris, Joshua; Si, Jingyu; Ding, Tianyao; Chen, Junhong; Qu, Deyang
Abstract: Sodium and potassium ion batteries (SIBs and PIBs) hold promise as potential low-cost and large-scale energy storage devices due to the earth abundance of sodium and potassium. Among all proposed anode materials, red phosphorus (P) has been recognized as a promising candidate owing to its high theoretical capacities for use in both SIBs and PIBs (2596 mA h g −1 for Na3 P and 843 mA h g −1 for KP); however, its intrinsic insulating property and large volume change during cycling lead to poor cycling and rate performance. To overcome these issues, we have designed and synthesized a carbon nanotube-backboned mesoporous carbon (TBMC) material for the impregnation of red P. The TBMC was synthesized by a synchronic growth of resorcinol-formaldehyde resin/SiO2 on carbon nanotubes, followed by carbonation of the resin and removal of the SiO2 . The resulting TBMC was then infiltered with red P at elevated temperatures, forming a P@TBMC composite. In this unique composite, multi-walled carbon nanotubes facilitate the electron transfer due to the high content of sp 2 carbon, while the mesoporous carbon layers offer voids to load appropriate amounts of P but leave enough space to alleviate the huge volume change of the P upon sodiation/potassiation. Therefore, the P@TBMC composite exhibits excellent cycling performance and rate capability as the anode for both SIBs and PIBs. For example, the P@TBMC composite shows a high reversible desodiation capacity ( 1000 mA h g −1 at 0.05 A g −1 ), superior rate performance ( 430 mA h g −1 retained at 8 A g −1 ), and excellent cycle life (no capacity decay for 800 cycles at 2.5 A g −1 ). More impressively, the P@TBMC, as an anode of PIBs, exhibits electrochemical performance superior to all the reported anodes for PIBs, namely, delivering a reversible capacity of 500 mA h g −1 0.05 A g −1 and a stable capacity of 244 mA h g −1 at 0.5 A g −1 for 200 cycles. The design based on confining active materials into hybrid carbon nanostructures integrated with highly conductive sp 2 carbon and porous carbon is expected to shed light on the development of high-performance electrode materials for metal-ion batteries and other energy storage systems. Graphical abstract: A carbon nanotube-backboned mesoporous carbon (TBMC) material has been fabricated to load red phosphorus (P), forming a P@TBMC composite as superior anode material for sodium/potassium-ion batteries. The carbon nanotube in the TBMC facilitates electron transfer while the mesoporous carbon allows for addressing the huge volume change of red P upon sodiation/potassiation, thereby leading the P@TBMC to high capacity, excellent cycling performance, and good rate capability. fx1 Highlights: A carbon nanotube-backboned mesoporous carbon (TBMC) material was synthesized. Red phosphorus was incorporated into the mesopores of TBMC. The P@TBMC composite exhibited high capacities and excellent cycleability for both electrochemical sodium and potassium storage.